Through the lens of Good Participatory Practice: Findings and lessons learned from the healthcare worker subcommittee of the COVID-19 Healthcare Worker Exposure Response and Outcomes Registry - Mei Lin Chen-Lim; Jayne F. Koellhoffer; Kisha Batey Turner; Martha Summerlin; Anoop George; Eileen Handberg; Daryl Lawrence; Syed Hasan Naqvi; Emily O’Brien; Lauren Cohen; Patty McAdams; Laura Webb; et al. (Journal of Clinical and Translational Science)
Participant representation, including the Good Participatory Practice guidelines, in the design and execution of clinical research can profoundly affect research structure and process. Early in the COVID-19 pandemic, an online registry called the Healthcare Worker Exposure Response and Outcomes (HERO) Registry, was launched to capture the experiences of healthcare workers (HCWs) on the pandemic frontlines. It evolved into a program that distributed COVID-19-related information and connected participants with COVID-19-related research opportunities. Furthermore, a subcommittee of HCWs was created to inform the COVID-19-related clinical research, engagement, and communication efforts. This paper, coauthored by the HERO HCW subcommittee, describes how it was formed, the impact of community participation on the HERO Registry and Research Program, reflections on lessons learned, and implications for future research. Engagement of the HCW Subcommittee resulted in representing their lived experience and ensured that their perspectives as HCWs were incorporated into the HERO Research. The strategies not only supported recruitment and retention efforts but also influenced the HERO research team in framing research questions and data collection pertinent to the participant community. This experience demonstrated the importance of having participants’ input as expert advisors to an investigative team in their research efforts during a global health emergency.